Univerzální rezervační systém v cloudu - Bulín, Martin (Vysoké učení technické v Brně. Fakulta informačních technologií, 2015)
Tato bakalářská práce se zabývá návrhem a implementací univerzálního rezervačního systému v cloudu. Velkou část této práce tvoří přehled poskytovatelů cloudu a již existujících rezervačních systémů. Dále se práce zabývá návrhem a implementací rezervačního systému. Na tomto systému si ukážeme výhody cloudu. V závěru práce se zabývám škálovatelností cloudu a testováním vytvořeného systému v cloudu Amazon Web Services.

This bachelor thesis describes design and implementation of universal reservation system in cloud. Main part of this thesis includes review of cloud providers and existing reservation systems. Furthermore this academic paper deals with proposal and implementation of the reservation system. This system can show us the benefit of the cloud. In the conclusion I deal with scalability of cloud and testing created system in Amazon Web Services cloud.
Universal Reservation System in Cloud
Keywords: Cloud; Rezervační systém; Amazon Web Services; Elastic Compute Cloud; Relational Database Service; PHP; škálovatelnost; Cloud; Reservation system; Amazon Web Services; Elastic Compute Cloud; Relational Database Service; PHP; scalability